Design and Photoelectric Performance of Perfect Solar Absorber Based on GaAs Grating - Liu, Bin; Wu, Pinghui; Li, Yan; Zhu, Hongyang; Lv, Li (Frontiers in Materials, 2022)
In recent years, solar energy has received extensive attention as a clean and renewable energy. We present a perfect broadband solar absorber based on tungsten and semiconductor GaAs in this paper. The structure of GaAs grating-GaAs film-W substrate has been proposed. And the finite time domain difference method (FDTD) has been used for the numerical simulation of the model. Broadband absorption has been realized in the 500nm-1850nm, by adjusting the parameters of geometry to excite high-efficiency surface plasmon resonance. The absorption spectrum of the structure can be changed by adjusting the geometric parameters to meet different needs. The proposed absorber has incidence insensitive (0-60°) and high short-circuit current characteristics. The structure is simple and easy to manufacture, and has superior photoelectric properties to be application in photothermal conversion, collection and utilization of solar energy.